Performance and enteric methane emission of growing beef bulls from different genetic groups subjected to two supplementation strategies grazing tropical grass in the rainy season - Simioni, T. A. [UNESP]; Messana, J. D. [UNESP]; Silva, L. G. [UNESP]; Brito, L. F. [UNESP]; Torrecihas, J. A. [UNESP]; Granja-Salcedo, Y. T. [UNESP]; Vito, E. San [UNESP]; Lage, J. F.; Reis, R. A. [UNESP]; Berchielli, T. T. [UNESP] (Elsevier, 2022)
Improving livestock production through nutrition and breeding can increase efficiency and has the potential to mitigate methane (CH4) emissions. Additionally, supplementing beef cattle in the rainy season balances the dietary protein:energy (P:E) ratio, which can increase animal performance and reduce energy losses from CH4 production. Therefore, the objective of this study was to evaluate the effect of supplementation strategy (SS) and genetic group (GG) on the intake, digestibility, performance, and enteric CH4 emissions of growing beef bulls grazing tropical grass during the rainy season. One hundred sixty-two growing beef bulls averaging (mean ± SD) 10 ± 2 months old and 262 ± 31 kg of initial body weight (BW) were distributed, according to their BW, in a randomized complete block design in a 2 × 3 factorial arrangement. Factors included (1) two SSs (mineral supplementation at 0.3 g/kg of BW per day and a corn-based supplementation at 3 g/kg of BW per day) and (2) three GGs (Nellore [NN], ½Senepol½Nellore [SN], and ½Angus½Nellore [AN]). Animals were allocated in 12 paddocks composed of Urochloa brizantha (A. Rich.) Stapf. cv. Xaraés for 99 days during the rainy season. Regardless of the GG, the intakes of total DM, supplement DM, OM, CP, aNDFom, EE, and NFC were increased in animals supplemented with a corn-based supplement. The SN bulls had a greater digestibility of DM, OM, and CP, and animals supplemented with a corn-based supplement had greater CP and EE digestibility. There was an interaction between GG and SS for NFC digestibility, which was decreased in AN animals fed a corn-based supplement. However, the corn-based supplementation improved the animal's performance and carcass characteristics as demonstrated by the increase of final BW (kg), ADG (kg), REA (cm2), and FT (mm). Moreover, NN animals fed a corn-based supplement showed an increase in ADG (kg). An interaction between SS and GG was observed for GPH (kg/ha) and CaG (kg), with the greatest values observed in NN and SN animals supplemented with a corn-based supplement. Enteric CH4 emissions (g/d, g/kg of DMI, and g/kg of dOM) were lower in animals fed a corn-based supplement. A decrease in CH4 emissions (g/d) was observed in SN compared to NN animals. In addition, there was an interaction between SS and GG for CH4 emissions (g/kg of CaG), with the lowest values for NN and SN animals supplemented with a corn-based supplement. Taken together, our results demonstrate that corn-based supplementation is an effective nutritional strategy for use in the rainy season, especially for NN and SN genetic groups, to improve animal's performance and carcass characteristics and to decrease enteric CH4 emissions, per unit of product, of growing beef bulls grazing tropical grass.
Keywords: Body weight gain; Carcass; Energy supplement; Enteric fermentation; Greenhouse gas; Nellore; Ruminant nutrition